2008
DOI: 10.1007/s10800-008-9618-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plating parameters and solution chemistry on the voiding propensity at electroplated copper–solder interface

Abstract: Interfacial voiding in solder joints formed with Sn-Ag-Cu solder alloys and electroplated Cu was examined as a function of the plating solution chemistry and parameters. Galvanostatic Cu plating of *10 lm thick Cu films was performed in a commercially available plating solution, and in model generic plating solutions. Analysis of the current voltage behavior along with Secondary Ion Mass Spectrometry studies of organic impurity content of two plated and a wrought copper samples, yielded a conclusion that for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 24 publications
13
93
0
Order By: Relevance
“…Dimitrov's group [16,17,[33][34][35] also studied the impurity effect since 2008 by using various additive combinations including PEG, SPS, and Cl − . The individual use of PEG or Cl − resulted in a lower overpotential in the electrodeposition of Cu, but the use of PEG + Cl − (nominated as PC) caused an increment in the overpotential, showing that PEG is a suppressor and needs to co-work with the Cl − ions.…”
Section: Effects Of Impurity On Interfacial Reactions Of Electroplatementioning
confidence: 99%
“…Dimitrov's group [16,17,[33][34][35] also studied the impurity effect since 2008 by using various additive combinations including PEG, SPS, and Cl − . The individual use of PEG or Cl − resulted in a lower overpotential in the electrodeposition of Cu, but the use of PEG + Cl − (nominated as PC) caused an increment in the overpotential, showing that PEG is a suppressor and needs to co-work with the Cl − ions.…”
Section: Effects Of Impurity On Interfacial Reactions Of Electroplatementioning
confidence: 99%
“…PEG ? Cl -, an increase in the SPS in the deposit was registered in the range 0.5-5.0 mA cm -2 [13,14]. Accordingly, higher voiding propensity was found in Cu deposits with a higher impurity level.…”
Section: Introductionmentioning
confidence: 97%
“…To assess the quality of electroplating to the voiding propensity, studies reported by our research group have shown that voiding in the IMC Cu 3 Sn can be ''turned on'' and ''turned off'' by monitoring the factors that govern the electrodeposition of Cu from the acidic copper sulfate solution that are largely responsible for the impurity incorporation termed to be the primary cause to void evolution in the IMC [13][14][15]. The impurities associated with voiding came from the additives used in the Cu electrodeposition [13,14], i.e., polyethylene glycol (PEG), SPS, and the chloride ions (Cl -) that are indispensable in today's industrial acid Cu electroplating solution [6,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of Cu-solder reaction, many studies have reported that Cu plating conditions such as additives are related to microvoid formation at the CuCu 3 Sn interface, affecting the final solder joint reliability. [13][14][15][16][17] In case of Ni-solder reaction, it is reported that the Ni-P plating bath life affects the brittle fracture behavior of Sn-Ag-Cu solder joints. 18 However, few studies have investigated the effect of Ni-P plating conditions on solder joint properties.…”
Section: Introductionmentioning
confidence: 99%